1987
DOI: 10.1161/01.cir.76.6.1344
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow distribution within skeletal muscle during exercise in the presence of chronic heart failure: effect of milrinone.

Abstract: Recent studies suggest that, in the presence of heart failure, the capability of skeletal muscle to utilize delivered flow may be impaired due to maldistribution of blood flow within working muscle. Similarly, this mechanism could explain the failure of drugs to improve maximal oxygen consumption (VO2max) immediately. Accordingly, we assessed muscular blood flow distribution (ml/min/g, radioactive microspheres, 15 + 5 gm) among and within working muscle, V02max, and arterial lactate in a rat preparation of myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…In heart failure, skeletal muscle underperfusion emerges predominantly in oxidative working muscle. 28 Inhibition of NO synthesis and release by N G -nitro-L-arginine methyl ester (L-NAME) is most effective in limiting blood flow to oxidative working muscle, but the inhibitory effect of L-NAME on blood flow in these muscle fibers appears to be attenuated in chronic heart failure. 29 Thus, redistribution of blood flow within skeletal muscle appears to emerge in heart failure owing to endothelial dysfunction, possibly secondary to chronic deconditioning.…”
Section: See P 2709mentioning
confidence: 99%
“…In heart failure, skeletal muscle underperfusion emerges predominantly in oxidative working muscle. 28 Inhibition of NO synthesis and release by N G -nitro-L-arginine methyl ester (L-NAME) is most effective in limiting blood flow to oxidative working muscle, but the inhibitory effect of L-NAME on blood flow in these muscle fibers appears to be attenuated in chronic heart failure. 29 Thus, redistribution of blood flow within skeletal muscle appears to emerge in heart failure owing to endothelial dysfunction, possibly secondary to chronic deconditioning.…”
Section: See P 2709mentioning
confidence: 99%
“…In addition, fluid and sodium retention in heart failure and structural alterations of the vessel wall may contribute to increased vascular stiffness and changes REVIEW in local flow [14,15]. It is important to note that a redistribution of blood flow is seen not only between the regional beds but also within the muscle itself [16]. DREXLER et al [16] demonstrated, using the radiolabelled microsphere technique, that the flow to muscles with predominant white, glycolytic fibres (white portion of the vastus lateralis and white part of the gastrocnemius) is maintained in rats with CHF in contrast to the blood flow to muscles with predominantly oxidative fibres, such as the soleus and the red portion of the gastrocnemius.…”
Section: Factors Contributing To Exercise Limitationmentioning
confidence: 99%
“…It is important to note that a redistribution of blood flow is seen not only between the regional beds but also within the muscle itself [16]. DREXLER et al [16] demonstrated, using the radiolabelled microsphere technique, that the flow to muscles with predominant white, glycolytic fibres (white portion of the vastus lateralis and white part of the gastrocnemius) is maintained in rats with CHF in contrast to the blood flow to muscles with predominantly oxidative fibres, such as the soleus and the red portion of the gastrocnemius. As blood flow is proportional to the oxidative capacity of muscle fibres [17,18], it is possible that these findings support the interpretation that in heart failure a shift takes place from aerobic (oxidative) to anaerobic metabolism.…”
Section: Factors Contributing To Exercise Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart failure was secondary to chronic myocardial infarction. This model has been previously described (Selye et al, 1960;Pfeffer et al, 1985a; and is widely used to test the effects of drugs (Drexler et al, 1987;Gay et al, 1987). In this model, left ventricular end diastolic pressure is increased, dp/dt max + is decreased and peripheral blood flow is unaltered at rest but not during exercise (Drexler et al, 1987).…”
Section: Discussionmentioning
confidence: 99%